Effects of conjugated linoleic acids, fish oil and soybean oil on the growth performance, carcass traits, lipid characteristic and PPARs mRNA expression in broiler chickens - Royan, Maryam (2012)
The conjugated linoleic acids (CLA) are known to decrease hepatic lipid deposition and overall lipid metabolism in selected animal models. These properties can be employed to reduce body fat accumulation in food animals, as in broiler chicken. In fact, every 1 % decrease in the chicken’s body fat would result in the average Malaysian eating 300 g less fat for a year from chicken meat, based on per capita chicken meat consumption figures for 2010. However, the anti-lipogenic effects of CLA are variable and complicated because of the differences in animal species, diet composition and possibly their interactions with other dietary fatty acids. We hypothesized that CLA effects on fat metabolism in broiler chickens could be altered by the presence of dietary n-3 and n-6 fatty acids. Hence, fish oil (rich source of n-3 fatty acids) and soybean oil (rich source of n-6 fatty acids) were used in this trial. This study aimed to investigate the effects of dietary conjugated linoleic acids, fish oil, soybean oil and their mixtures, as well as palm oil on broiler chickens. A total of 560 day-old Ross 308 male broiler chickens allotted randomly into 7 equal treatment groups and used in 42 days experimental period. All chicks were fed a starter corn-soybean meal-based diet for 10 days. The treatment diets used were adjusted to be isocaloric and isonitrogenous comprising the corn-soybean meal plus specific dietary fat supplements consisting of conjugated linoleic acid (CLA), fish oil, soybean oil, palm oil or their combinations. The dietary fats were included in the experimental diets at 7% for single fats and 3.5% + 3.5% for dual mixes, and because of the lower metabolisable energy of palm oil as compared to PUFAs, its inclusion rate was about 12%. The conjugated linoleic acids supplement used in this study was LUTA-CLA 60, containing 60% conjugated linoleic acid. Therefore the dietary inclusions of 7 and 3.5% LUTA-CLA 60 were effectively supplying 4.2 and 2.1% CLA, respectively. The treatment groups were 7% soybean oil (SO), 7% LUTA-CLA 60 (CL), 7% fish oil (FO), 3.5% LUTA-CLA 60+ 3.5% soybean oil (CLSO), 3.5% fish oil + 3.5% soybean oil (FOSO), 3.5% LUTA-CLA 60 + 3.5% fish oil (CLFO) and 12% palm oil (PO). The experimental diets were used at grower (11-28 d) and finisher (29-42 d) phases and performance data were collected for each period. Tissue and serum sampling was carried out at the end of experiment (42 d). The high level of palm oil inclusion in the diet did not adversely affect chicken’s feed intake or growth rate. The lowest weight gains were recorded for birds from FO and CL groups during the grower (24.2 g/b/d) and finisher (50.9 g/b/d) phases, respectively. The FO diet also reduced the feed intake of chickens (34.5 g/b/d) while dietary conjugated linoleic acids had no effect on feed intake regardless of its dosage and combinations with other fats. It was also found that palm oil supplemented at about 12 % (w/w) increased the weight of abdominal fat pads significantly (%2.4 of live weight), while higher conjugated linoleic acids content of the CL group increased post slaughter liver weights (%3.3 of live weight) (P<0.05). Lipid contents of the breast tissues were higher in the PO (%2.46), SO (%2.02) and FO (%2.02) groups (P<0.05) versus others (%1.11-1.55). Birds from the FO group had the highest amount of fats in their thigh muscles (%3.94) (P<0.05). Fish oil was more effective in reducing serum undesired lipoproteins (comparable effect with soybean oil), and CL diet enhanced serum favourite HDL fraction. It was also evident that conjugated linoleic acids in combination with soybean oil or fish oil resulted in less fat accumulation in both thigh and breast tissues, as compared to birds treated with soybean oil or fish oil only. Deposition and enrichment of longer chain n-3 fatty acids were also higher in the breast tissue of birds treated with conjugated linoleic acid in combination with fish oil (275 mg/100 g meat) as compared to the fish oil only treatment (254 mg/100 g meat). The treatment oils demonstrated different effects on PPAR genes. The PPARγ gene was up-regulated significantly in the PO group, whereas the levels of adipose PPARγ gene expression were no different across treatments containing conjugated linoleic acids, fish oil, soybean oil or the mixture of these fats. On the other hand PPARα gene expression in the liver tissue was up-regulated in response to dietary fish oil inclusion and the differences were significant for both FO and CLFO treatments compared to PO, SO and CL treatments. In conclusion, the results of the present study showed that the dietary 7% fish oil or 4.2% CLA supplements reduced broiler chicken performance. This combination resulted in the enrichment of n-3 in chicken meat. The combination of CLA with soybean oil on the other hand increases the CLA levels in the chicken meat. The PPARα gene demonstrated anti-lipogenic effects when it is upregulated in the presence of CLA. Changes in the abdominal fat deposition in broiler chickens could be attributed to both PPARα (in hepatocytes), and PPARγ in adipocytes. Lower abdominal fat deposition was achieved by up-regulating the PPARα (of hepatocytes), in tandem with the down-regulation of PPARγ in the adipocytes.